Robust optimization in cloud computing - Saransh Bansal. (2012)
Cloud computing provides a computing platform for the users to meet their demands in an efficient, cost-effective way. Virtualization technologies are used in the clouds to aid the efficient usage of resources. Virtual machines (VMs) are utilized to satisfy the user needs and are placed on physical machines of the cloud for effective usage of hardware resources and electricity in the cloud. Optimizing the number of resources used helps in cutting down the power consumption by a substantial amount and the cost paid by the user for acquiring the virtual machines respectively. Cloud providers in general offer users two payment plans, i.e., reservation and on-demand plans for resource provisioning. However, since the reservation plan has to be acquired in advance, it may not fully meet future demands in which the on-demand plan can be used to guarantee the availability to the user. The author aims on translating the existing optimal virtual machine placement (OVMP) algorithm problem which is solved using stochastic integer programming to robust linear optimization.